Christopher Nolan the iconic filmmaker and his work : unofficial and unauthorised - Nathan, Ian (White Lion, 2022)
An engaging and in-depth examination of the work of Christopher Nolan, one of the most revered directors working in modern cinema. Best known for his cerebral, often nonlinear, storytelling, over the course of 15 years of filmmaking, Nolan has gone from low-budget independent films to working on some of the biggest blockbusters ever made
Keywords: Nolan, Christopher -- 1970-; Electronic books; Bildband